The Fundamentals of Islamic Business Ethics in Developing a Just and Sustainable Islamic Economy: Dasar-Dasar Etika Bisnis Islam Dalam Membangun Ekonomi Syariah Yang Berkeadilan Dan Berkelanjutan - Ika Susanti; Kurniawan Ramadhani (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2026)
Islamic business ethics constitute a fundamental pillar in the development of a fair, sustainable, and value-oriented economic system. The increasing complexity of modern business practices has generated various ethical challenges, including fraud, exploitation, unfair competition, information asymmetry, environmental degradation, and economic inequality. These phenomena highlight the urgent need for an ethical framework capable of balancing economic objectives with moral responsibilities. This article aims to analyze the fundamental principles of Islamic business ethics and their relevance to the contemporary development of the Islamic economic system. This study employs a qualitative approach through library research by examining classical and contemporary literature, including the Qur’an, Hadith, books, and scholarly journal articles related to Islamic economics and business ethics. The findings indicate that Islamic business ethics are founded upon several core principles, namely tawhid, justice, honesty, trustworthiness, responsibility, and ihsan. These principles guide economic actors in conducting business activities that prioritize public welfare, transparency, accountability, sustainability, and social justice. Furthermore, the implementation of Islamic business ethics contributes significantly to strengthening public trust, promoting sustainable business practices, reducing economic disparities, and achieving prosperity in accordance with the objectives of Islamic law (maqashid al-shariah). Therefore, Islamic business ethics remain highly relevant in addressing contemporary economic challenges and in supporting the development of a just and sustainable Islamic economic system.